An overview of the idiopathic inflammatory myopathies - Albayda, Jemima (Henry Stewart Talks, 2017)
Clinical presentation of the idiopathic inflammatory myopathies, Classification criteria for myositis, Myositis antibodies and clinical associations, Diagnostic tools and evaluation of myositis, Treatment strategies for myositis